Acceleration of ion recombination reaction rates in cold dark clouds through spontaneous polarization charge on CO ice mantles. Issue Volume 15:Issue S350(2019) (April 2019) - Cassidy, Andrew; Rosu-Finsen, Alexander; Lasne, Jérôme; McCoustra, Martin R. S.; Field, David
Abstract: We propose a role for CO ice mantles in ion recombination reactions, and demonstrate how the subsequent fall in the degree of gas phase ionization decreases the time required for cloud collapse under gravity by a factor of 5-6. Experimental results demonstrate that CO films prepared at cryo-temperatures spontaneously harbour electric fields immediately upon growth. Using what is known from observations about prestellar cloud conditions in the ISM, we explain how this phenomenon can lead to an acceleration in ion recombination reaction rates. The result is a pathway for cloud collapse to occur before cloud disruption by supernova remnants.